Penambahan Kombinasi Spirulina dan Tepung Wortel Pada Pakan Udang Rebon Terhadap Tingkat Kecerahan Warna dan Pertumbuhan Ikan Koi (Cyprinus carpio) (Jurnal Pertanian Terpadu, 2023)
Koi fish are a freshwater fish that widespread interest because of the variety of patterns and the color combination. One of the attempt to enhance the quality of color is to add a source of pigment in the food that will help the improving color process in a fish's body. This study aims to determine an optimum dose of increasing combination the Spirulina and carrot flour on the feed towards the brightness levels of color and growth of the Koi fish. The study used Randomized completely design (RCD) that consist four treatments and three repetitions. The combination dosage used in each treatment is P1 (100% rebon shrimp flour), P2 (60% rebon shrimp flour + 5% spirulina + 35% carrot flour), P3 (60% rebon shrimp flour + 10% Spirulina + 30% carrot flour) and P4 (60% rebon shrimp flour + 15% Spirulina + 25% carrot flour). The study is done for 30 days with the frequency of feeding four times a day at 8:00 a.m., 12:00 a.m., 4:00 p.m. and 8:00 p.m.. Feed is fed on the fish to their fullest (ad-satiation). The study shows that adding spirulina and carrot flour combinations to the rebon shrimp feed has a real impact on changing color levels of TCF (Toca Color Finder), red dimensional changes, growth of the long and the weight of the koi fish (P 0,05). TCF color level changes (Toca Color Finder), red color dimensional changes, l *a*b color changes, the highest growth of long and weight found in P3 (60% rebon shrimp flour + 10% spirulina + 30% carrot flour).Keywords: Koi fish, (Cyprinus carpio), Spirulina, Carrot Flour, Quality Color